Solving second-order linear ordinary differential equations by using interactive software - Coelho, Celestino (2017)
Differential equations constitute an area of great theoretical research and applications in several branches of science and technology. The scope of this work is to present new software that is able to show all the steps in the process of solving a linear second-order ordinary differential equation with constant coefficients.